Why coaching matters: exploring the interplay of teacher self-regulation and well-being with a longitudinal multigroup model - Bührer, Zippora; Wolfgramm, Christine; Berweger, Simone; Keck Frei, Andrea; Bieri Buschor, Christine (Frontiers in Psychology, 2025)
IntroductionSelf-regulation is considered an important aspect of professional competence that promotes teachers’ well-being. It involves controlling thoughts, feelings and actions to pursue goals, deal adaptively with challenges and cope with stress. For early career teachers, these skills are crucial for their health and staying in the profession. However, longitudinal studies which position self-regulation as a personal resource for teachers’ well-being remain scarce. The aim of our study was to examine the reciprocal interplay between teachers’ self-regulation and well-being (i.e., emotional exhaustion and work engagement), and the impact of self-management training and subsequent professional online coaching on these relations.MethodsThe study was conducted as part of a professional development course for early career teachers (N = 273), in which the participants were randomly assigned to a standardized training program. Using multigroup structural equation modeling, we compared two treatment groups (training-only, training plus online coaching) with a control group regarding the structural relations.ResultsThe model comparison revealed significant differences: Self-regulation predicted both work engagement and emotional exhaustion, but only in the group that received training plus coaching. Furthermore, work engagement predicted self-regulation across all groups.DiscussionWe conclude that self-regulation can serve as an effective personal resource for teachers well-being, under the condition that it is activated as resource and supported. In pursuing challenging goals, coaching may offer crucial support in each phase of the self-regulation process. This longitudinal study contributes to a differentiated view of self-regulation in the field of professional development, and clarifies the conditions under which it serves as an effective individual resource for teachers well-being.